Metagenomic and Functional Profiling of Endophytes from Indonesian Medicinal Plants: Potentials for Sustainable Bioprospecting - Sakina, Zafira Naja; Imam Supriyadi; Budi Santoso (Westscience Press, 2025)
Indonesia's extraodinary plant biodiversity remains underutilised in microbial bioprospecting, despite its vast potential to support sustainable biotechnological innovation. This study aims to explore and characterise endophytic microorganisms associated with selected Indonesian medicinal plants, focusing on their genetic and functional traits relevant to bioactive compound production. Addressing a gap in integrative profiling, the study adopts a qualitative literature-based methodology, synthesising findings from over 30 peer-reviewed, Scopus-indexed studies published between 2015 and 2024. These studies involve next-generation sequencing, biosynthetic gene cluster (BGC) analysis, and in vitro functional assays. Notably, endophytes isolated from plants such as Curcuma longa, Andrographis paniculata, and Phyllanthus niruri harbour diverse and unique BGCs, including non-ribosomal peptide synthetases (NRPS) and polyketide synthases (PKS), which are linked to antimicrobial, enzymatic, and plant growth-promoting activities. The originality of this study lies in its interdisciplinary synthesis bridging microbial ecology, genomics, and biotechnology, contributing to the theoretical advancement of microbial symbiosis and offering practical implications for natural product development, sustainable agriculture, and Indonesia's emerging bioeconomy